HONORER’S MASTER’S HUMANITY BETWEEN MYTHS AND REALITIES - Ika, Heni; Wahyu, Wahyu; Hidayat, Yusuf (JURNAL SOCIUS, 2023)
The government's low attention to the welfare of honorary teachers at SMA Muhammadiyah 2 Banjarmasin is indeed very concerning. In fact, the obligations carried out by honorary teachers are no different from PNS teachers. The honorary teachers continue to carry out the same obligations as PNS teachers, namely to guide and become good educators for each student, but in reality, this great task and responsibility in educating students is not commensurate with the wages they receive. As a result, it puts honorary teachers at SMA Muhammadiyah 2 Banjarmasin at risk of being less prosperous in their quality of life.The type of research in this article is descriptive qualitative research where the data are obtained directly from honorary teachers at SMA Muhammadiyah 2 Banjarmasin with the number of informants as many as 4 (four) teachers. Data collection techniques using observation and interviews. Then using data analysis in the form of data collection, data presentation and drawing conclusions. The results of the research in this article arein terms of welfare, the standard of living can be said to have not been achieved because they have to work harder to get something decent.With a very low salary income, honorary teachers are still able to fulfill their welfare. One of the needs that are met is the aspect of Physical Needs.